Self Disclosure, Perilaku Asertif dan Kecenderungan Terhindar dari Tindakan Bullying - Meilena, Tika; ., Suryanto (Persona:Jurnal Psikologi Indonesia, 2015)
The purpose of this study is to examine the correlation between self disclosure andassertive behavior with tendency to avoid bullying. Research variables were measured usinga tendency to avoid bullying scale, self disclosure scale and assertive behavior scale. Subjectswere 56 students at 1st grade SMP Tajinan Malang. Data were analyzed using regressionanalysis. The results showed that self disclosure and assertive behavior significantly associatedwith tendency to avoid bullying. Separately, self disclosure did not correlate significantly withtendency to avoid bullying. Meanwhile, assertive behavior has a positive correlation withtendency to avoid bullyingKeywords: Tendency to avoid bullying, Self disclosure, Assertive behavior